Tourism research frontiers beyond the boundaries of knowledge - Chambers, Donna; Rakic, Tijana (Tourism social science series ;, 2015)
This book recognizes that while tourism research has undoubtedly penetrated and gone beyond a number of knowledge frontiers, frontiers are never static, but are constantly shifting and changing form in the context of a dynamic environment. This book therefore is a much needed contribution which acknowledges the imperative for continuous innovation and renewal in tourism research if it is to remain relevant. In this regard the book contains original papers which span a number of creative topics and debates and which transcend existing frontiers of tourism knowledge, including pop-culture tourism, gospel festivals as heterotopia, tourism and elections, articulations of the concept of tourismization and tourism of spiritual growth and critical explorations of the tourism image of Switzerland as represented in right wing visual rhetoric. Importantly this original text also includes novel discussions of sustainability and destination evolution and network dynamics. The book concludes with reflections from the editors on additional frontiers of tourism research and knowledge still to be traversed.